Relationships of the New World cichlid genus Hypsophrys Agassiz 1859 (Teleostei: Cichlidae), with diagnoses for the genus and its species - Chakrabarty, Prosanta; Sparks, John S. (Zootaxa, 2007)
Two monotypic Neotropical cichlid genera, Hypsophrys Agassiz 1859 and Neetroplus Günther 1867, are well known but poorly diagnosed. The possession of a single supraneural (versus two for most Middle American species), a strongly rounded snout with a small and slightly subterminal mouth (versus straight snout profiles with terminal mouth) provide morphological support for the sister-group relationship of Hypsophrys and Neetroplus recovered in recent molecular phylogenetic analyses. Based on these shared features Neetroplus is synonymized with Hypsophrys. In addition, the senior synonym Hypsophrys unimaculatus should no longer be improperly suppressed in favor of the more familiar, but junior, H. nicaraguensis.